BS EN 55011 Fragments 2-7. Industrial, scientific and medical equipment. Radio-frequency disturbance characteristics. Limits and methods of measurement. Requirements for air-gap wireless power transfer (WPT). (19th June 2020) - British Standards Institution,
No abstract available